The intervening domain is required for DNA-binding and functional identity of plant MADS transcription factors - Xuelei Lai (Nature Portfolio, 2021)
MADS transcription factors regulate multiple aspects of plant development. Here the authors show that the intervening I domain is conserved in both type I and type II plant MADS lineages and contributes to the functional identity of the protein by influencing both DNA binding activity and dimerisation specificity.